(untitled) (Bangladesh Veterinarian, 2010)
Identification of risk factors is important for the design of control programmes for mastitis in cows. Information about farms and management was collected at a farm visit. California Mastitis Test (CMT) was performed to assess sub-clinical mastitis, and cows, udder and milk were examined for clinical mastitis. A total of 347 lactating cows from 83 farms in the dry season (November - February) and 388 lactating cows from 89 farms in the wet season (June - October) were studied. The overall prevalence of mastitis was 19.9% and 44.8% in dry and wet seasons, respectively. The prevalence of mild mastitis was 17.3% and 40.7%, whereas that of moderate mastitis was 2.6% and 4.1% in dry and wet seasons, respectively. The prevalence of mastitis was higher (P<0.01) in wet than in dry season. On average, 18.7% quarters had mastitis during the wet season and 6.9% in the dry season. In the dry and wet seasons, respectively, 63.9% and 11.2% had completely dry floors, and the prevalence of mastitis was 22.6% and 30.0%. On the other hand, 88.8% and 36.1% of 83 farms had partly or completely wet and soiled floor and the prevalence of mastitis was 40.0% and 59.5% in the dry and wet seasons, respectively. Udder cleanliness, milk yield and peri-parturient diseases significantly (P<0.01) increased the risk of mastitis. The prevalence of mastitis is regarded as quite high. Dry and clean floor to keep cow’s udder and teat clean would help control mastitis in the dairy farms of Bangladesh. DOI: 10.3329/bvet.v26i2.4951 Bangl. vet. 2009. Vol. 26, No. 2, 54-60